Indolo-naphthyridine-6,13-dione Thiophene Building Block for Conjugated Polymer Electronics: Molecular Origin of Ultrahigh n-Type Mobility - Stoichko Dimitrov (Chemistry of Materials, 2016)
Herein, we present the synthesis and characterization of four conjugated polymers containing a novel chromophore for organic electronics based on an indigoid structure. These polymers exhibit extremely small band gaps of ∼1.2 eV, impressive crystallinity, and extremely high n-type mobility exceeding 3 cm2 V s–1. The n-type charge carrier mobility can be correlated with the remarkably high crystallinity along the polymer backbone having a correlation length in excess of 20 nm. Theoretical analysis reveals that the novel polymers have highly rigid nonplanar geometries demonstrating that backbone planarity is not a prerequisite for either narrow band gap materials or ultrahigh mobilities. Furthermore, the variation in backbone crystallinity is dependent on the choice of comonomer. OPV device efficiencies up to 4.1% and charge photogeneration up to 1000 nm are demonstrated, highlighting the potential of this novel chromophore class in high-performance organic electronics.